SEMANTIC CHANGE OF WORDS ENTERED INTO ANOTHER LANGUAGE THROUGH THE PROCESS OF LANGUAGE BORROWING: A CASE STUDY OF ARABIC WORDS IN BENGALI - Hasan, Mahade (PEOPLE: International Journal of Social Sciences, 2015)
This research paper aimed to study different aspect of semantic changes what Arabic words have faced in Bengali. The relationship between Arabic and Bengali, two languages which belong to two different language families, has been the topic of research by scholars for a long period of time. The main objective of this paper is identifying Arabic words in Bengali those have either changed meaning or shifted away from the denotations of their original meanings and finding out the reason of their change in meaning. This paper followed the descriptive-qualitative method. The data has been collected from the Bengali dictionary “Person-Arabic elements in Bengali” and then data has been analyzed to find out semantically changed Arabic words. The discussion concludes that there is a high frequency of Arabic origin words in Bengali, which are a product of borrowing. However, the researcher explained some selected words under particular category whether the word took broader meaning or narrowed, positive meaning or negative, metaphor or metonymy or it has totally shifted away from the original meaning. For example: the Arabic word “Zhiaarat” stands for visit or meet (in general) in Arabic while it is used in Bengali only for the meaning of visiting the grave including holy grave of Prophet Muhammad (pbuh) and Holy Ka’ba. Here, this word has taken positive but narrow meaning. It is called Amelioration with narrowing according to the linguistic approach.